Recognition Of Punjabi Script Character And Number For Multiple Fonts (International Journal of Engineering and Computer Science, 2015)
In this paper there is telling about a easy and quick algorithm for recognition of Punjabi script which included both character and number. This algorithm is designed for multiple fonts because the fonts used in newspaper, magazines and books are different. We apply morphological operations on binary images.  There is no need of any knowledge of phase or any kind of memory. Main advantage of this algorithm is its correctness to identify Punjabi characters and number.  Only a very few work can be traced for character recognition of Indian scripts especially for the North Indian scripts like Punjabi. Input to the system is the scanned images from newspaper, magazines and old books.